Գրիգոր Նազիանզացու պահոց ճառերի նորահայտ մեկնությունները Տոնապատճառ ժողովածուում - Օհանջանյան, Աննա («Նաիրի» հրատ.)
The Tonapatchar collection contains commentaries on church feasts and was designed mainly for didactical and polemical purposes. Several recensions of this collection (up until the late 13th century) are known to scholars. The most significant and influential recensions are by Vardan Hałbatecʻi (d. ca. 1193/95) and Vardan Arewelcʻi (ca. 1200-1271), renowned theologians of the Hałbat school. Both authors wrote a number of commentaries specifically to be included in the Tonapatchar collection. Most of them, however, to this day remain anonymous. The commentaries on Gregory Nazianzen‟s First (1) and Second (45) Paschal Orations are anonymous. The current paper focuses on two different versions of commentaries on Gregory Nazianzen‟s Second Paschal Oration (45) found in Vardan Hałbatecʻi‟s (MS M2021) and Vardan Arewelcʻi‟s (MS M4139) recensions of Tonapatchar. Some textual hints along with exegetical peculiarities in the given micro-historical context support the hypothesis that the authors are Vardan Hałbatecʻi‟ and Vardan Arewelcʻi‟. Several copies of Vardan Hałbatecʻi‟s version have survived, and it was included in Tonapatchar‟s later recensions, while Vardan Arewelcʻi‟s commentary can only be found in the manuscript M4139. Сборник Тонапатчар (“Толкования на Праздники”) содержит толкования и разъяснения на церковные праздники и создан в дидактических и полемических целях. Специалистам давно знакомы несколько редакций данного сборника, которые создавались вплоть до конца XIII века. Самые важные и наиболее влиятельные редакции принадлежат знаменитым богословам Ахпатской школы Вардану Ахпатеци (ум. 1193/95) и Вардану Аревелци (ок. 12001271). Оба автора написали несколько комментариев специально для включения в сборник Тонапатчар, и многие из них до сих пор оставались анонимными. Комментарии на Первое (1) и Второе (45) Слово на Пасху принадлежат к их числу. В данной статье рассматриваются две разные версии толкования на Второе (45) Пасхальное Слово Григория Назианзина, сохранившиеся в редакциях Тонапатчара Вардана Ахпатеци (рук. 2021 Матенадарана) и Вардана Аревелци (рук. 4139 Матанадарана). Некоторые текстовые и экзегетическиe особенности в данном микро-историческом контексте позволяют приписать эти комментарии Вардану Ахпатеци и Вардану Аревелци. Версия толкования, составленная Варданом Ахпатеци, многократно копировалась и была включена в последующие редакции Тонапатчара, тогда как текст толкования Вардана Аревелци можно найти лишь в единственном экземпляре в рукописи Матенадарана 4139.
Keywords: Հայկական եկեղեցիներ; Տոնակատարություններ